2016
DOI: 10.3390/ijms17060953
|View full text |Cite
|
Sign up to set email alerts
|

Novel Double-Hit Model of Radiation and Hyperoxia-Induced Oxidative Cell Damage Relevant to Space Travel

Abstract: Spaceflight occasionally requires multiple extravehicular activities (EVA) that potentially subject astronauts to repeated changes in ambient oxygen superimposed on those of space radiation exposure. We thus developed a novel in vitro model system to test lung cell damage following repeated exposure to radiation and hyperoxia. Non-tumorigenic murine alveolar type II epithelial cells (C10) were exposed to >95% O2 for 8 h only (O2), 0.25 Gy ionizing γ-radiation (IR) only, or a double-hit combination of both chal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 51 publications
1
10
0
Order By: Relevance
“…Space-relevant radiation can induce oxidative damage in various tissues of rodents. Lung tissue from mice showed significant oxidative damage, including DNA damage, protein nitrosative stress, and lipid peroxidation after exposure to radiation, similar to space [ 73 , 74 , 75 ]. Mice exposed to low-doses of ionizing radiation exhibited oxidative damage and apoptosis in the retina [ 76 ].…”
Section: Iron Overload and Its Link To Spaceflight-induced Oxidatimentioning
confidence: 99%
“…Space-relevant radiation can induce oxidative damage in various tissues of rodents. Lung tissue from mice showed significant oxidative damage, including DNA damage, protein nitrosative stress, and lipid peroxidation after exposure to radiation, similar to space [ 73 , 74 , 75 ]. Mice exposed to low-doses of ionizing radiation exhibited oxidative damage and apoptosis in the retina [ 76 ].…”
Section: Iron Overload and Its Link To Spaceflight-induced Oxidatimentioning
confidence: 99%
“…Nordsmark et al ( 17 ) demonstrated that increased tumor partial O 2 pressure enhanced IR response in mammary carcinoma. Pietrofesa et al ( 18 ) reported that exposure to the combination of IR + O 2 increased DNA damage and cell death compared with the individual exposures to IR or O 2 alone. However, how a high concentration of O 2 pretreatment affects the efficacy of cervical cancer radiotherapy has not been fully elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…In further studies using space-relevant radiation (proton radiation), we have shown that LGM2605 (the synthetic version of SDG) acts as a mitigator of radiation-induced increases in inflammatory signals (cytokines, chemokines) in human lung sections (huPCLS) [22]. LGM2605 is a potent scavenger of radiation-induced reactive oxygen species (ROS) and active chlorine species (ACS), and can reduce the ionizing species arising from radiation [23,24,25,26]. However, more importantly, it is also an inhibitor of several proinflammatory signaling pathways that upregulate cytokines, chemokines, and adhesion molecules [24,27].…”
Section: Introductionmentioning
confidence: 99%